1993
DOI: 10.1177/104063879300500210
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelas in Caged Laying Chickens and Suspected Erysipeloid in Animal Caretakers

Abstract: Erysipelas was diagnosed in 2 succeeding caged layer flocks housed in the same building and was characterized clinically by sudden death. At necropsy, lesions comprised generalized congestion, hemorrhages in the skeletal muscles and visceral organs, and swelling of liver, spleen, and kidney with or without large irregular zones of necrosis. Focal to massive hepatic necrosis was seen histologically with minimal or no inflammatory reaction. Erysipelothrix rhusiopathiae was cultured from internal organs of affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Erysipelothrix tonsillarum, a different but closely related species to E. rhusiopathiae, is considered to be non-pathogenic in pigs and chickens (Takahashi et al 1994). Outbreaks of erysipelas have been reported in turkeys, chickens and ducklings (Takahashi et al 1994), with outbreaks of E. rhusiopathiae in chickens being reported from flocks raised in free-range, indoor litter-based and caged-housed systems (Mutalib et al 1993;Fossum et al 2009;Stokholm et al 2010). While large outbreaks of erysipelas have been reported only infrequently in chickens, commercial producers and researchers from various parts of the world have reported outbreaks more frequently in recent years, coincident with the expanded use of free-range housing systems (Wang et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Erysipelothrix tonsillarum, a different but closely related species to E. rhusiopathiae, is considered to be non-pathogenic in pigs and chickens (Takahashi et al 1994). Outbreaks of erysipelas have been reported in turkeys, chickens and ducklings (Takahashi et al 1994), with outbreaks of E. rhusiopathiae in chickens being reported from flocks raised in free-range, indoor litter-based and caged-housed systems (Mutalib et al 1993;Fossum et al 2009;Stokholm et al 2010). While large outbreaks of erysipelas have been reported only infrequently in chickens, commercial producers and researchers from various parts of the world have reported outbreaks more frequently in recent years, coincident with the expanded use of free-range housing systems (Wang et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Erysipelas in poultry often involves acute infection of individuals within the flock, and since most affected birds die there are also economical consequences for the farmer (Bricker and Saif 2003). The ways of introduction of E. rhusiopathiae into poultry facilities has not been definitely established but contaminated material from the outdoor area could be one way, as well as presence of rodents in the houses (Mutalib et al 1993). When the bacteria are present in the facility, entry through skin lesions or mucous membranes are possible transmission routes to the birds (Bricker and Saif 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Dermanyssus gallinae has also been suggested as a potential vector of pathogens causing chicken diseases such as Newcastle disease, fowl spirochaetosis, chicken pox, fowl cholera, encephalitis, erysipelas and salmonellosis (Zeman et al 1982;Durden et al 1993;Chauve 1998;Chirico et al 2003;Valiente Moro et al 2007b. The zoonotic aspects of some of these pathogens should also be considered as D. gallinae, in the absence of its main host, may bite humans and also other mammals such as dogs, cats, rodents and horses, causing pruritus and dermatitis (Brockis 1980;Mutalib et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…2,8 Economically significant outbreaks in chickens have also occasionally occurred in Japan 16,18 and other countries. 4,12,15,25 It is reported that, in Japan, 5.5% of chicken sera examined had high titers of growth agglutination antibody against E. rhusiopathiae, 22 implying that the bacterium could potentially be present among chickens in the field. Erysipelas in the poultry industry might therefore be an animal hygiene issue to be controlled by turkey and chicken farmers.…”
mentioning
confidence: 99%
“…5 Most field cases of avian erysipelas 8,15,18 have therefore been diagnosed based on postmortem inspection, including pathological examination and the identification of E. rhusiopathiae isolated from the lesions. However, these diagnostic methods cannot be performed antemortem, and confirmation of diagnosis is a slow process.…”
mentioning
confidence: 99%